Trends of Epidemiological and Demographic Indicators of COVID-19 in India - Manoj Kumar Gupta; Pankaj Bhardwaj; Akhil Dhanesh Goel; Suman Saurabh; Sanjeev Misra (Journal of Infection in Developing Countries)
Introduction: This study was planned to assess the trends of epidemiological indicators and demographic determinants related to the COVID-19 in India.